Sustainable Self-Management, Resilience and Management-School Support in Work-School Conflict - Artika Nukleusada Ningrum; Mafizatun Nurhayati (ARE Publisher, 2026)
Education is a very important and necessary thing for everyone. Therefore, there are still many people who, despite already working, wish to continue their studies to a higher level for various reasons. However, in reality, based on a preliminary survey that has been conducted, many students experience conflicts during their studies. Hence, the need for this research. This study aims to investigate the effects of resilience coping and sustainable self-management on work-school conflict, as well as the functions of school and management assistance because of what they frequently feel that their academic obligations and professional expectations are out of balance. Using a quantitative explanatory approach, Master's students at Mercu Buana University were participated in this study. A survey was used to gather data, and SEM-PLS was used for analysis. The test results that have an influence in reducing work-school conflict are resilience coping and sustainable self-management, moderated by school support. This research is expected to provide practical suggestions on how workers who continue their education can effectively manage conflicts between working and study Based on the reference sources and the Conservation of Resources (COR) theory used as the theoretical foundation of this research.